2014
DOI: 10.1186/1748-7161-9-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compliance to a Rigo System Cheneau brace and a specific exercise programme on idiopathic scoliosis curvature: a comparative study: SOSORT 2014 award winner

Abstract: BackgroundThere is controversy as to whether conservative management that includes wearing a brace and exercises is effective in stabilising idiopathic scoliosis curves. A brace only prevents progression of the curve and has been shown to have favourable outcomes when patients are compliant. So the aim of this study was to: determine the effect of compliance to the Rigo System Cheneau (RSC) brace and a specific exercise programme on Idiopathic Scoliosis curvature; and to compare the Quality of Life (QoL) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 71 publications
1
20
1
1
Order By: Relevance
“…Of those prescribing PT or PSSE, the number prescribing either or both was similar. In addition, despite the impression that PT and PSSE are more widely used in Europe [ 7 – 9 , 15 , 19 , 20 , 22 ] compared to North America, our study showed that there was no difference in prescribing patterns among the respondents based on region. Although, there was no difference in prescribing pattern for standard PT based on the surgeon’s years in practice, older surgeons were more likely to prescribe PSSE.…”
Section: Discussioncontrasting
confidence: 82%
“…Of those prescribing PT or PSSE, the number prescribing either or both was similar. In addition, despite the impression that PT and PSSE are more widely used in Europe [ 7 – 9 , 15 , 19 , 20 , 22 ] compared to North America, our study showed that there was no difference in prescribing patterns among the respondents based on region. Although, there was no difference in prescribing pattern for standard PT based on the surgeon’s years in practice, older surgeons were more likely to prescribe PSSE.…”
Section: Discussioncontrasting
confidence: 82%
“…With respect to motivation, personal experience during exercise was the most commonly identified barrier, with pain, 18,27,48,83,85 boredom, 8,18,22,96 and an overall lack of enjoyment 2,83,88 identified. Barriers related to capability included psychological traits (eg, lack of confidence, forgetfulness), 18,39,78,83 physical traits (eg, fatigue), 29,83 and not understanding the purpose of the exercises. 2,18…”
Section: Barriers To Exercise Therapy Adherencementioning
confidence: 99%
“…Bezüglich der LQ haben wir bei den Patienten, die eine Tragezeit von über 22 Stunden angaben, einen signifikant höheren SRS-Gesamt-Score sowie einen höheren Wert in der Kategorie "Mentale Gesundheit" gefunden. Dies ist vereinbar mit den Ergebnissen von Rivetti und Kollegen, welche höhere SRS-Scores bei Patienten mit hoher Compliance fanden [17]. Dennoch zeigten andere Studien auch, dass IAS-Patienten unter Korsetttherapie eine niedrigere Lebensqualität in den Sektionen Aktivität und Selbstwahrnehmung genossen als vergleichbare Patienten, die nur beobachtet wurden [46].…”
Section: Diskussionunclassified